Marcos and the Philippines - Lawson, Don (Watts, 1984)
Presents a brief history of the Philippines and discusses the dictatorship of President Marcos and the present political controversy which surrounds it. Offers speculations about the future of this troubled country.
Keywords: Marcos, Ferdinand E <1917-1989> -- (Ferdinand Edralin) -- Juvenile literature; Marcos, Ferdinando Edralin -- 1917-1989; Politik; Geschichte; Philippines -- Politics and government; Philippines -- Politics and government -- 1946- -- Juvenile literature; Philippinen